Expanding the Mutational Spectrum of CRLF1 in Crisponi/CISS1 Syndrome. Issue 4 (6th March 2014) - Piras, Roberta; Chiappe, Francesca; Torraca, Ilaria La; Buers, Insa; Usala, Gianluca; Angius, Andrea; Akin, Mustafa Ali; Basel‐Vanagaite, Lina; Benedicenti, Francesco; Chiodin, Elisabetta; El Assy, Osama; Feingold‐Zadok, Michal; et al.
<x xml:space="preserve">Abstract</x> Expanding the mutational spectrum of CRLF1 in Crisponi/CISS1 Syndrome Mutations in the CRLF1 gene are responsible for Crisponi/Cold Induced Sweating Syndrome Type 1 (CS/CISS1), a rare autosomal‐recessive disorder characterized by four distinct features, such as hyperthermia and feeding difficulties in the neonatal period, scoliosis, and cold‐induced sweating in the evolutive period. In this study we expanded the mutational spectrum of CRLF1 in the CS/CISS1 syndrome to a total of 35 variants in 56 patients from 47 families. The highest prevalence is found in Sardinia, Turkey and Spain. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>